Seasonally and spatially referenced estimates of recreational shore-angling effort, catch composition, catch rates and total catch in the Goukamma Marine Protected Area, South Africa. Issue 4 (2nd December 2016) - Attwood, CG; van Zyl, CS; Lombard, AT; McCagh, C
Abstract : A roving creel survey of the recreational shore fishery along the 16.4-km coastline in the Goukamma Marine Protected Area on the south coast of South Africa was conducted from 2009 to 2011. Some 838 patrols were stratified equally among months, areas and years, but intentionally biased towards weekends. Angler densities at Buffalo Bay and Groenvlei were 0.59 and 0.28 anglers km−1, respectively. Weekend densities were double to quadruple weekday densities and fishing during winter was more popular than during summer. Area, habitat and distance to access points explained variation in angler densities. Shannon–Wiener diversity in catches declined from 2.18 in an earlier (1993–2002) survey to 1.79. Although the order of species abundance in the catches remained largely unchanged, blacktail Diplodus capensis dominance increased to 57.3% by number, at the expense of galjoen Dichistius capensis . Habitat explained 27% of the variance in catch composition. The catch per unit effort (CPUE) for the top nine species ranged from 0.19 to 6.35 fish 100-h−1. The CPUE of all species, except spotted grunter Pomadasys commersonnii, declined. Blacktail and galjoen CPUE declined by 17% and 77%, respectively. The total catch estimate was 2 986 fish y−1. Transgressions of size limits were common. The results suggest that the fishery is overexploited and that catch rates are declining.